The effects of awareness-raising through stimulated recall on the repeated performance of the same task and on a new task of the same type - Sheppard, C.; Ellis, Rod (2018)
The study explores the effects of intervening between the performance of the same task and whether these effects transfer to a new task. 40 Japanese university students completed the same monologic narrative task three times and then performed a new task of the same type (Time 4). 20 students just performed the tasks (the task-repetition group). The other 20 engaged in a stimulated recall procedure after the initial performance of the first task (the stimulated recall group). In both groups, structural complexity increased from Time 1 to Time 2 and was maintained, including in the new task. In contrast, accuracy remained the same for both groups when the same task was repeated and decreased notably in the new task. Fluency improved in both groups when the same task was repeated but declined when the new task was performed. However, performance of the new task was still significantly better than at Time 1. No differences were evident in complexity and accuracy between the task-repetition and the stimulated recall groups over time. The stimulated recall group demonstrated greater fluency than the task-repetition group when repeating the same task but not the new task. The chapter concludes with comments on the potential of stimulated recall as a means for enhancing the effects of task repetition.